Weight bias among UK trainee dietitians, doctors, nurses and nutritionists. Issue 4 (21st November 2012) - Swift, J. A.; Hanlon, S.; El‐Redy, L.; Puhl, R. M.; Glazebrook, C.
Abstract: Background: Trainee dietitians, nutritionists, nurses and doctors will direct the future of obesity treatment and prevention. To do so effectively, they must be willing and able to engage empathically with overweight and obese people. The present study aimed to assess weight bias among UK trainee healthcare professionals and to investigate the factors predicting weight bias, both static and potentially modifiable. Methods: A self‐completed questionnaire collected data on demographics, weight and height, the Fat Phobia Scale (F‐scale), and the Beliefs about Obese People (BOAP) scale from 1130 students. Results: Overall, participants demonstrated significant levels of fat phobia [F‐scale score mean (SD) = 3.8 (0.5)]. Only 1.4% of participants could be said to have expressed 'positive or neutral attitudes' (i.e. achieved a F‐scale score ≤ 2.5). Hierarchical multiple regression revealed that lower fat phobia (as measured by the F‐scale) was uniquely predicted by a higher self‐reported body mass index, being on the Nursing BSc course and a stronger perception that obesity is not under a person's control (as measured by the BOAP scale). Conclusions: There are unacceptable levels of weight bias among UK students training to become nurses, doctors, nutritionists and dietitians. The results of the present study suggest that a promising approach for future interventions would be the provision of balanced education about the controllability of obesity, focusing upon genetic and environmental factors, as well as diet and exercise.